2014
DOI: 10.1016/j.jchromb.2014.02.057
|View full text |Cite
|
Sign up to set email alerts
|

A survey of liquid chromatographic–mass spectrometric analysis of mercapturic acid biomarkers in occupational and environmental exposure monitoring

Abstract: High-performance liquid chromatography/mass spectrometry (HPLC/MS) is sensitive and specific for targeted quantitative analysis and is readily utilized for small molecules from biological matricies. This brief review describes recent selected HPLC/MS methods for the determination of urinary mercapturic acids (mercapturates) which are useful as biomarkers in characterizing human exposure to electrophilic industrial chemicals in occupational and environmental studies. Electrophilic compounds owing to their react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 52 publications
0
13
0
1
Order By: Relevance
“… 9 10 Urine concentrations of the 7 urinary metabolites VOCs, including benzene, toluene, xylene, styrene, as well as formaldehyde, were measured using gas chromatography/tandem mass spectroscopy. 11 12 Urinary metabolites of benzene and xylene consisted of trans,trans-muconic acid (t,t-MA), and o-toluic acid and p-toluic acid, respectively. Urinary metabolites of styrene consisted of mandelic acid (MA) and phenylglyoxylic acid (PGA), and the urinary metabolite of formaldehyde consisted of thiazolidine-4-carboxylic acid (TZCA).…”
Section: Methodsmentioning
confidence: 99%
“… 9 10 Urine concentrations of the 7 urinary metabolites VOCs, including benzene, toluene, xylene, styrene, as well as formaldehyde, were measured using gas chromatography/tandem mass spectroscopy. 11 12 Urinary metabolites of benzene and xylene consisted of trans,trans-muconic acid (t,t-MA), and o-toluic acid and p-toluic acid, respectively. Urinary metabolites of styrene consisted of mandelic acid (MA) and phenylglyoxylic acid (PGA), and the urinary metabolite of formaldehyde consisted of thiazolidine-4-carboxylic acid (TZCA).…”
Section: Methodsmentioning
confidence: 99%
“…The results of that study demonstrated the presence of significantly higher levels of urinary mercapturic acid metabolites of benzene, acrolein, and crotonaldehyde in the cooks compared to the controls. Mercapturic acids are formed by reaction of these compounds or their metabolites with cellular glutathione, followed by metabolic processing and excretion, and are widely used biomarkers for exposure to volatile toxicants and carcinogens [ 20 , 21 ]. Benzene is a carcinogen while acrolein and crotonaldehyde are powerful irritants and DNA-reactive compounds which may play some role in lung carcinogenesis [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results are surprising in view of the well-established activity of this pathway based on in vitro studies and the ease of detection of urinary mercapturic acids of other xenobiotics such as acrolein, acrylonitrile, and benzene [37]. One possible explanation for the low levels of these phenanthrene metabolites in human urine is that they are excreted mainly in feces, which were not collected or analyzed in this study.…”
Section: Discussionmentioning
confidence: 75%